2018
DOI: 10.1038/s41598-018-20080-2
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential synchrony of neurons in anterior cingulate cortex plays a pivotal role in generation of neuropathic pain

Abstract: The pathophysiology of neuropathic pain generation has not been fully investigated. Previous studies have primarily focused on changes in the properties of single neurons in the brain after nerve injury; however, little is known concerning the role of neuron-to-neuron connections in neuropathic pain pathogenesis. Synaptic transmission potentiation in anterior cingulate cortex (ACC) has been confirmed to be responsible for the formation of neuropathic pain. Thus, analysis of interneuronal connections in the ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Because both the ACC and primary somatosensory cortex, which are located in the pain ascending pathway, receive nociceptive inputs from the medial thalamus, the increased activity of pyramidal cells in both areas reflects their participation in a cerebral cortical circuit involved in chronic pain. In fact, electrophysiological studies show the activation of many pyramidal neurons of ACC layer II/III after nerve injury [ 59 , 60 ], and some studies show that inhibiting the hyperactivity or plasticity of pyramidal neurons in the ACC lessens the development of chronic pain [ 59 , 61 ]. Combining our current results with those of previous studies, we speculated that rapamycin modulates the interaction between GluA1-PSD-95 and NR2B-PSD-95 by regulating the mTOR signaling pathway that controls synaptic plasticity in the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Because both the ACC and primary somatosensory cortex, which are located in the pain ascending pathway, receive nociceptive inputs from the medial thalamus, the increased activity of pyramidal cells in both areas reflects their participation in a cerebral cortical circuit involved in chronic pain. In fact, electrophysiological studies show the activation of many pyramidal neurons of ACC layer II/III after nerve injury [ 59 , 60 ], and some studies show that inhibiting the hyperactivity or plasticity of pyramidal neurons in the ACC lessens the development of chronic pain [ 59 , 61 ]. Combining our current results with those of previous studies, we speculated that rapamycin modulates the interaction between GluA1-PSD-95 and NR2B-PSD-95 by regulating the mTOR signaling pathway that controls synaptic plasticity in the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers [ 32 ] further proved that the ACC was a brain region closely linked to pain-related emotions. It has been found that the long-term enhancement of ACC activity may be one of the mechanisms of persistent emotional change in patients with chronic pain caused by nerve injury or peripheral inflammation [ 33 36 ]. Our data showed that the PWT of the model group was significantly lower than that of the control group at 16 d. The group with the ACC lesion did not differ from the control group at 16 d. However, the pain-related aversion developed from 2 d to 16 d, and there was no manifestation of aversion after ACC lesioning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in recent years have found that there is a close relationship between the ACC and neuropathic pain. 7,[10][11][12][23][24][25] Neuropathic pain model was set up by chronic constriction injury of the left sciatic nerve of rats. The left HWL to thermal and mechanical stimulation, by hot plate and Randall Selitto Test respectively, were used to evaluate the antinociception.…”
Section: Discussionmentioning
confidence: 99%